KEGIATAN STORYTELLING MELALUI APLIKASI WHATSAPP SEBAGAI ALTERNATIF MENUMBUHKAN LITERASI DASAR DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA CIREBON - Firda Rahmadianty Lestari; Tine Silvana Rachmawati; Elnovani Lusiana (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2022)
Storytelling activities at Dinas Perpustakaan dan Kearsipan Kota Cirebon have switched to using the WhatsApp application since the Covid-19 pandemic. This initiative is one of the alternatives to cultivate basic literacy even in limited conditions. This study aims to determine the implementation of storytelling activities through WhatsApp application at Dinas Perpustakaan dan Kearsipan Kota Cirebon and its application based on the basic literacy model. The research method used is qualitative with a case study approach. Data collection techniques were carried out through observation, interviews, documentation, and literature study. The results of this study indicate that the implementation of storytelling activities through WhatsApp application is carried out in four stages, namely opening, storytelling activities, crafting activities, and closing. This activity is also implemented based on the basic literacy model proposed by (Ferguson, n.d.) with four components, including reading & writing, speaking & listening, counting & calculating, and perception & drawing. The application is carried out with various activities according to its components, where there are different interests and developments among storytelling participants. From this research, it can be concluded that the WhatsApp application can be an alternative media to carry out storytelling activities in cultivate basic literacy.